2005
DOI: 10.1002/cm.20080
|View full text |Cite
|
Sign up to set email alerts
|

The unconventional myosin-VIIa associates with lysosomes

Abstract: Mutations in the myosin-VIIa (MYO7a) gene cause human Usher disease, characterized by hearing impairment and progressive retinal degeneration. In the retina, myosin-VIIa is highly expressed in the retinal pigment epithelium, where it plays a role in the positioning of melanosomes and other digestion organelles. Using a human cultured retinal pigmented epithelia cell line, ARPE-19, as a model system, we have found that a population of myosin-VIIa is associated with cathepsin D-and Rab7-positive lysosomes. Assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…MYO7A has been reported previously to function in the motility of RPE phagosomes , and to associate with lysosomes in an RPE cell line [Soni et al, 2005].…”
Section: Discussionmentioning
confidence: 98%
“…MYO7A has been reported previously to function in the motility of RPE phagosomes , and to associate with lysosomes in an RPE cell line [Soni et al, 2005].…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, it was shown that myosin VIIA associates with melanosome via Slac-c/MyRIP and suggested that it transports melanosomes (44,45). The association of myosin VIIA with lysosomes was also reported (46). The studies described above have suggested the two potential functions of myosin VIIA, i.e.…”
Section: Actin-attached Hydrolysis Pathway (Amt-amdp)-mentioning
confidence: 90%
“…Antibodies were against the following proteins: Caprin-1 (rabbit, 1:200) (Solomon et al, 2007); TIA-1 (C-20) (goat polyclonal antibody, 1:200; Santa Cruz Biotechnology); myosin VIIa (138-1) [mouse, 1:250; developed by Soni et al (Soni et al, 2005) and obtained from the Developmental Studies Hybridoma Bank (Department of Biology, University of Iowa, Iowa City, IA)]. Secondary antibodies (all Invitrogen) were used at 1:1000: goat anti-(rabbit Ig) conjugated to Alexa Fluor 488 or Alexa Fluor 546; goat anti-(mouse Ig) conjugated to Alexa Fluor 568 or Alexa 635; donkey anti-(goat Ig) conjugated to Alexa Fluor 488; and rabbit anti-(goat Ig) conjugated to Alexa Fluor 568.…”
Section: Immunofluorescence and Cochlea Slicingmentioning
confidence: 99%